In the Trenches : A Russian Woman Soldier's Story of World War I - Dubinskai︠a︡, Tatʹi︠a︡na Leonidovna, 1902-1990 (Book collections on Project MUSE., 2020)
"Set in Russia in the year 1916, In the Trenches is based on the true story of the author's life during WWI. Fourteen-year-old Zina runs away from home to serve on the Eastern Front as a soldier in the Russian army."--